1989
DOI: 10.1073/pnas.86.9.3114
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and sequencing of cDNAs encoding the entire rat fatty acid synthase.

Abstract: Overlapping cloned cDNAs representing the entire sequence of the rat fatty acid synthase mRNA have been isolated from a cDNA library and sequenced. Authenticity of the cDNA clones was supported by hybridization to fatty acid synthase mRNA and by amino-terminal sequencing of 39 fatty acid synthase CNBr fragments. The full-length fatty acid synthase mRNA is 9156 nucleotides long and includes an 84-nucleotide 5' noncoding region, a 7515-nucleotide coding sequence, and a 1537-nucleotide 3' noncoding region; a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(107 citation statements)
references
References 24 publications
5
100
0
Order By: Relevance
“…Each of the N-terminal and C-terminal halves of the Orf B protein shows striking sequence similarity to their counterparts in Orf A. The alignment of these four 'half-proteins' with each other, with the sequence of rat fatty-acid synthase [27] and with the sequence of 6-methylsalicylate synthase from Penicillium patulum [21], is shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…Each of the N-terminal and C-terminal halves of the Orf B protein shows striking sequence similarity to their counterparts in Orf A. The alignment of these four 'half-proteins' with each other, with the sequence of rat fatty-acid synthase [27] and with the sequence of 6-methylsalicylate synthase from Penicillium patulum [21], is shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…By that time, the multifunctional enzymes still were thought to be stable assemblies of individual enzymes, and only in the early 1970s it became clear that the type I FASs in fact consist of multifunctional polypeptide chains encoded by large genes, and not of assembled individual enzymes (Schweizer et al 1973 ;Stoops et al 1975). Domain mapping, genetic studies and the publication of the primary structures of animal and yeast FAS in the 1980s showed that although both systems are classified as ' FAS type I ', the animal and yeast enzymes have a radically different domain organization and therefore evolved along two unrelated lines (Amy et al 1989 ;Mohamed et al 1988;Schweizer et al 1986). …”
Section: The Chemistry Of Fatty Acid Biosynthesismentioning
confidence: 99%
“…Construction of the Transferase Expression Plasmids-The plasmid pFAS54, which consists of nucleotides 642-2544 of the fatty acid synthase cDNA (5) and is believed to encode the entire transferase domain of the fatty acid synthase flanked by regions encoding part of the ␤-ketoacyl synthase and possibly the dehydrase domains (2), was used as template DNA for the PCR-based engineering of two different length constructs both encoding the transferase (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%